Efektivitas Komunikasi Partisipatoris dalam Pengembangan Masyarakat Islam: Sebuah Analisis Berdasarkan Prinsip-prinsip Teori Dialektika Relasional - Hidayat, Rahmat Hidayat; Muhammad Solihin; Ahmad Sultra Rustan (STAI Bumi Silampari, 2025)
Communication, as a broad and multidimensional field of study in the social sciences, encompasses a variety of theories and approaches, one of which is relational dialectical theory. This theory, derived from the thought of Mikhail Bakhtin, views life as a dialogical arena where individuals constantly interact with conflicting desires and needs in the context of their relationships. Leslie Baxter, one of the key figures in the development of this theory, emphasises that relationships are dynamic and require ongoing attention to achieve success and satisfaction. Relational dialectic theory provides a comprehensive framework for understanding the complexity of relationships, recognising that each individual experiences and navigates tensions in relationships in unique ways. Therefore, communication plays a crucial role in managing and balancing the various tensions and contradictions that arise in human interactions. Relational dialectic theory can be defined as ‘the nexus of contradictions in personal relationships or the continual interaction between opposites or tendencies to oppose’. In the context of scientific research, this theory provides a powerful analytical framework for understanding the dynamics of interpersonal relationships. By recognising the inherent tensions in relationships, researchers can identify and explore the various factors that influence communication and satisfaction in relationships. This approach not only helps in understanding the basic mechanisms of relationships, but also provides insights into how individuals can manage contradictions and tensions to achieve more harmonious and satisfying relationships. In research, relational dialectics theory can be used to analyse how individuals balance the need for autonomy and attachment in relationships, how they manage the tension between openness and privacy, and how they handle the contradiction between stability and change. By understanding these dynamics, researchers can develop more effective communication strategies to improve the quality of interpersonal relationships. Therefore, relational dialectics theory provides not only a comprehensive theoretical framework, but also practical tools for managing the complexity of human relationships.